Resource allocation scheme in two-way multi-relay OFDM system - Xuan-wei LIANG; Qi ZHU; Guang-jun LIANG (Tongxin xuebao)
A joint optimization scheme for power allocation and subcarrier pairing under high SNR in two-way multi-relay OFDM system was proposed.Unlike those schemes in which relays use subcarriers separately,all the relays were allowed to forward signal on each subcarrier pair for providing much space diversity.With the constraint of total system power,the proposed scheme firstly allocated each relay power with Cauchy inequality with the assuming that the total relay power was fixed.Then the dichotomy was used to calculate the power allocation between the source node and the relay node by maximizing the equivalent channel gain for different subcarrier pairs.Lastly,the power of different subcarrier pairs was allocated by convex programming,and the subcarriers were paired by Hungarian algorithm to obtain the maximum system capacity.There was no optimal power allocation method with low complexity because of the complexity of the power allocation algorithm in two-way multi-relay networks.This algorithm greatly reduces the complexity of power allocation and simulation results show that the proposed scheme outperforms the relay selection scheme and the relays use subcarriers separately scheme.